Recording plant status and regeneration during single visits. (2019) - Walker, Kevin J.; Leach, Simon J.; Preston, Christopher D.; Humphrey, Thomas A.; James, Trevor J.; Pearman, David A.; Smith, Paul A.
No abstract available